An Empirical Study on Attrition and Causes of Attrition of B-school Faculty Members at Bangalore- A Requisite for Retention - Temkar V, Dr. Roopa; Kulshrestha, Dr. Shilpi (The journal of contemporary issues in business and government, 2023)
ln India, the growth of education sector, the vast diversity together with varying demographics has encouraged different players to invest in the sector. In the meantime, the consequent increase in income levels of average Indian household to spend on higher education has also added to this state[4]. Due to privatization and commercialization of education, many individuals are showing interest to invest on educational institutions. Such Institutes have to be driven with a quality orientation in teaching which depends mainly on infrastructure, course curriculum and quality faculty members. Therefore this needs dedicated and committed faculty members who in turn need a constant support and encouragement by the management of various institutions. The privatization and commercialization of higher education has resulted in certain practices which are not oriented towards the importance of human resources. Such poor practices lead to attrition of faculty members. Hence, teaching fraternity is in great demand, because of mushroomed growth of B-schools in today’s competitive education field. In spite of mushrooming of B-schools because of demand created for the programme, it has failed in providing employment opportunity for the graduates. This probably requires an open-minded management who welcomes the ideas and can bring solutions for different ailments of B-school. As like increase in number of management institutes, the faculty member’s strength should also be increased. Faculty member’s attrition has its impact on both individual and organization. At present there is need for retention of faculty members and also the steps that has to be taken jointly by the management and faculty members to enhance the performance of B-schools.